2004
DOI: 10.1063/1.1751225
|View full text |Cite
|
Sign up to set email alerts
|

Boron diffusion in amorphous silicon and the role of fluorine

Abstract: We demonstrate that boron diffuses at high concentrations during low-temperature thermal annealing in amorphous silicon pre-amorphized by germanium ion implantation. For a typical boron ultrashallow junction doping profile, concentrations as high as 2ϫ10 20 cm Ϫ3 appear to be highly mobile at 500 and 600°C in the amorphous silicon region before recrystallization. In crystalline silicon at the same temperatures the mobile boron concentration is at least two orders of magnitude lower. We also show that boron dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 13 publications
2
37
0
Order By: Relevance
“…Experiments [5][6][7][8][9][10] and theoretical calculations [11,12] seem to evidence B clustering within the regrown layer for high B concentrations. Sheet resistance measurements [5,[7][8][9] and the hump observed in secondary ion mass spectrometry (SIMS) profiles (associated to B diffusion in amorphous Si) [5,7,8,10] are consistent with active B concentrations up to a few times 10 20 cm −3 for regrowth temperatures around 600 • C, and higher levels can be reached if the regrowth takes place at higher temperatures [27]. The study of the formation of B clusters in amorphous Si requires a complex modeling.…”
Section: Simulation Modelmentioning
confidence: 97%
See 2 more Smart Citations
“…Experiments [5][6][7][8][9][10] and theoretical calculations [11,12] seem to evidence B clustering within the regrown layer for high B concentrations. Sheet resistance measurements [5,[7][8][9] and the hump observed in secondary ion mass spectrometry (SIMS) profiles (associated to B diffusion in amorphous Si) [5,7,8,10] are consistent with active B concentrations up to a few times 10 20 cm −3 for regrowth temperatures around 600 • C, and higher levels can be reached if the regrowth takes place at higher temperatures [27]. The study of the formation of B clusters in amorphous Si requires a complex modeling.…”
Section: Simulation Modelmentioning
confidence: 97%
“…The implantation cascades are simulated with a binary collision approximation code, MARLOWE [15], which generates the coordinates of the displaced atoms in the lattice along with those of the implanted atom. In our simulations of SPER samples, we directly read the B profile experimentally obtained just after the regrowth, which includes the experimentally observed B diffusion in amorphous Si [10].…”
Section: Simulation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 Conversely, theoretical calculations recently showed that the Si self-diffusion in a-Si is enhanced in presence of a high percentage of coordination defects, pointing out that selfdiffusion can be assisted by db or fb. 32 Similarly, B diffusion in a-Si was measured to be larger in the as implanted state than in the relaxed one, 10,11,33 showing peculiar features, such as a transient behavior and a dopant concentration dependence, which will be described in the next paragraph.…”
Section: A Defects and Diffusion In Amorphous Simentioning
confidence: 99%
“…2). 33 The immobile portion of the B profile (above 2 Â 10 20 B/cm 3 ) was attributed to B clustering in a-Si. Actually, the formation of B-B pairs during the very early stages of annealing at 550 C, while B is still in the amorphous phase of Si, has been evidenced by x-ray absorption near-edge spectroscopy measurements of p þ /n ultrashallow junctions realized by solid-phase epitaxy.…”
Section: B Main Features Of B Migrationmentioning
confidence: 99%